2019
DOI: 10.3389/fmicb.2019.02727
|View full text |Cite
|
Sign up to set email alerts
|

Oxalic Acid From Sesbania rostrata Seed Exudates Mediates the Chemotactic Response of Azorhizobium caulinodans ORS571 Using Multiple Strategies

Abstract: Chemotaxis toward seed exudates is important in the establishment of microbe–plant associations. The objective of this work was to explore whether organic acids from the seed exudates of Sesbania rostrata play a role in recruiting Azorhizobium caulinodans ORS571 in the plant rhizosphere. High-performance liquid chromatography (HPLC) was used to analyze the organic acid content in seed exudates of S. rostrata and to further determine their roles in A. caulinodans growth and chemotactic response. Succinic, aceti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Furthermore, our results were highly consistent with earlier reports that some bene cial bacteria associated with plants exhibit chemotaxis toward OAs in a dose-dependent manner (Liu et al 2019;Zhang et al 2013;Zhang et al 2014). As expected, the qRT-PCR on cheA relative gene expression levels in YP1 demonstrated that FA at 50 µM induced the highest increase in cheA gene transcript expression of all the OA treatments at that concentration (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, our results were highly consistent with earlier reports that some bene cial bacteria associated with plants exhibit chemotaxis toward OAs in a dose-dependent manner (Liu et al 2019;Zhang et al 2013;Zhang et al 2014). As expected, the qRT-PCR on cheA relative gene expression levels in YP1 demonstrated that FA at 50 µM induced the highest increase in cheA gene transcript expression of all the OA treatments at that concentration (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Effects of OAs on the growth of the representative P. notoginseng-associated CAEB strain in vitro An assay was designed to evaluate the effect of exogenous OAs at different concentrations on the growth of representative CAEB as previously described (Liu et al 2019). The bacterial cells were incubated overnight in 10 mL NB medium and then adjusted to an OD 600 of 0.1.…”
Section: Quantitative Capillary Assaysmentioning
confidence: 99%
“…Moreover, the addition of exogenous glycine or citric acid can increase the colonization of LG14-3 in the banana rhizosphere. Some carbon metabolites in plant root exudates can serve as food and as an energy source for rhizosphere microorganisms [5,47,48]. Similarly, citric acid supports the growth of LG14-3.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative analysis of OA secreted by S. latifolia in culture was carried out using high-pressure liquid chromatography (HPLC) (Agilent 1260 Infinity II Prime, Agilent, Santa Clara, CA, USA) [ 20 ]. S. latifolia mycelial discs were placed in the center of a sterile cellophane sheet overlayed on top of PDPA plates and incubated at 24 °C.…”
Section: Methodsmentioning
confidence: 99%